Association of abductor hip muscle atrophy with fall-related proximal femur fractures in the elderly - Erinç, Samet; Bozca, Mehmet Ali; Bankaoğlu, Müjdat; Çakırtürk, Süleyman; Yahşi, Yusuf; Özdemir, Hacı Mustafa (Injury, 2020)
•Fatty infiltration of the abductor muscle was more prominent on the fractured side than the control group in the patients with a proximal femur fracture.•However, atrophy scores for the gluteus medius muscle on the healthy side were not significantly different from scores in the control group.•Subjects with hip fractures showed trends towards lower hip muscle CSA and lower muscle HU (reflecting greater fatty infiltration of the musculature) than controls.•Abductor muscle atrophy and fatty tissue infiltration are major risk factors for fall-related injuries, especially in the elderly. The purpose of this study was to evaluate an association between fall-related intertrochanteric or femoral neck fractures and gluteus medius and minimus atrophy, furthermore, to find a correlation of whether any difference between femoral neck or intertrochanteric fracture and degree of muscle atrophy A retrospective review of 230 patients with intertrochanteric or femoral neck fracture, aged > 65 years, and 60 age- matched controls was performed. We assessed gluteus medius and minimus atrophy and calculated the cross-sectional area (CSA) and ratio of lean muscle to adipose infiltration (M/A ratio) for each muscle. The atrophy scores for the g.medius and g.minimus muscles on the fractured side were significantly higher than scores on the healthy side and scores in the control group. The atrophy scores for the g.medius on the healthy side were not significantly different from scores in the control group. The atrophy scores for g.medius were significantly different between the fractured side and the healthy side for all ages, the atrophy scores for g.minimus was significantly different in the patients aged over 75. There was no significant difference in the following parameters between the fractured side and healthy side of the patients aged 65 - 75 years; the atrophy score, CSA and M/A ratio. The patients have a lower CSA and M/A ratio on the fractured side than on the healthy side and lower CSA and M/A ratio than in the control group. However, there were no significant differences in the M/A ratio between the healthy side and the control group. CSA was not significantly different between the fractured side and healthy side in the male patients and in the patients with lower BMI (<30). There was no significant difference in the atrophy scores between subjects with intertrochanteric versus femoral neck fractures, the CSAs of the g.medius and g.minimus were significantly different between the intertrochanteric fracture and femoral neck fracture groups. The fractured sides showed greater g.medius and g.minimus muscle atrophy, which may be a predictor of fall-related hip fractures in the elderly. Gluteal muscle volume may be associated with proximal femur fracture subtype.